A Hamiltonian approach to the H2 decoupling of previewed input signals - Ferrante, A.; Marro, G.; Ntogramatzidis, Lorenzo (European Control Conference 2007 committee, 2007)
This paper addresses the H2 optimal decoupling of previewed inputs. In particular, the synthesis of a decoupling filter exploiting the preview is carried out by recasting the problem as a single finite-horizon LQ regulator, with a generalized quadratic termainal cost. The present approach is based on a computational attractive parametrization of the solutions of the associated Hamiltonian differential equation, and can also be applied for the solution of the dual problem, the H2 optimal fixed-lag smoothing problem.